Changes in the epidemiology of methicillin-resistant Staphylococcus aureus in a Greek tertiary care hospital, over an 8-year-period. - Pantazatou, Angeliki; Papaparaskevas, Joseph; Stefanou, Ioanna; Papanicolas, John; Demertzi, Elli; Avlamis, Athina (Int J Antimicrob Agents, 2003)
A total of 1019 non-replicate, consecutively isolated methicillin-resistant Staphylococcus aureus (MRSA) strains were collected from in-patients of a tertiary care general hospital in Athens, Greece, during the period 1994-2001. The susceptibility, resistance phenotypes and the dissemination of these isolates among hospital wards were studied. Total MRSA and gentamicin-resistant MRSA, as a proportion of the S. aureus isolates, increased from 33 and 9% in 1994 to 50.1 and 33.3% in 2001, respectively. Three main multi-resistant phenotypes predominated, representing 50.9% of the total MRSA isolates in 2001. MRSA strains susceptible to all antibiotics tested decreased to 1.9% in 1997 and again increased to 13.5% in 2001. A gradual decrease in the susceptibility of vancomycin during the 8-year-period was detected, but no vancomycin resistant S. aureus strains were isolated.
Keywords: Cross Infection; Drug Resistance, Multiple, Bacterial; Gentamicins; Greece; Hospitals, General; Humans; Methicillin; Methicillin Resistance; Microbial Sensitivity Tests; Retrospective Studies; Staphylococcal Infections; Staphylococcus aureus; Vancomycin